Switching biological disease-modifying antirheumatic drugs in patients with axial spondyloarthritis: results from a systematic literature review. Issue 2 (10th October 2017) - Navarro-Compán, Victoria; Plasencia-Rodríguez, Chamaida; de Miguel, Eugenio; Diaz del Campo, Petra; Balsa, Alejandro; Gratacós, Jordi
Abstract : Objectives: First, to investigate if switching biological disease-modifying antirheumatic drugs (bDMARDs) after the failure to prior bDMARD is efficacious in patients with axial spondyloarthritis (axSpA). Second, to evaluate the influence on this efficacy of (1) the reason to discontinue prior tumour necrosis factor inhibitor (TNFi), (2) changing the type of TNFi and (3) changing the target. Methods: A systematic literature review until January 2017 was performed using Medline, EMBASE and Cochrane databases. Longitudinal studies assessing clinical response after switching bDMARDs in patients with axSpA were analysed. Results: In total, 9 studies out of 1862 retrieved citations were included. Overall, the level of evidence was poor. In these studies, all patients received a TNFi as first bDMARD, 1956 patients switched to a second bDMARD (97% TNFi and 3% interleukin-17 inhibitors (IL-17i)) and 170 to a third bDMARD (all TNFi). Clinical response (Bath Ankylosing Spondylitis Disease Activity Index 50) after a second TNFi was achieved by 25%–56% of patients compared with 50%–72% after the first TNFi. Also, 47% of patients switching to IL-17i after a TNFi responded (Assessment of SpondyloArthritis international Society 40) compared with 66% in those who received IL-17i as first line. The response after switching was not influenced by the reason to discontinue, type of prior TNFi or changing the target. Conclusions: In patients with axSpA, switching to a second bDMARD (a TNFi or IL-17i) after prior TNFi is efficacious. Nevertheless, the clinical response is lower than the observed in patients naive to bDMARD. So far, the reason to discontinue prior bDMARD or the type of bDMARD has not been identified as predictor of response. Published evidence for switching to a third bDMARD is lacking.